(untitled) (Journal of the College of Basic Education, 2022)
The problem of the research lies in the need for women to make an improvement in the shape of the body and its functional efficiency, and this matter requires the development of a training program that includes special exercises that are concerned with the aesthetic aspect of the body in line with their capabilities and desires. The aim of the research is to identify some body measurements and functional variables for untrained women from the research sample, prepare water exercises (hydrotrapia) and special exercises that fit the capabilities of the research sample, and identify the effect of water exercises (hydrotrapia) associated with special exercises in some body measurements and functional variables of the research sample. The two researchers used the experimental approach to design one group, and the research sample was selected using the probability method of women aged 30-40 years and by (13) trainees. The training curriculum was implemented, which took (9) weeks and by three training units per week, and the number of training units reached (27) units. The researchers concluded that the training program that included hydrotrapia exercises and physical beauty exercises contributed to improving the shape of the body and raising the functional efficiency of the trainees